Литературоведческие расследования - Бухштаб Борис Яковлевич (Современник, 1982)
Экземпляры: РБ (20190820☮) / Инвентарный номер: 3048 / Цена: 00.40 / Авт.знак: Б94 / ГРНТИ: 17.09 / ББК: 83.3(2Рос=Рус)1